Editorial: Libraries and/as Extraction - Seale, Maura; Pagowsky, Nicole; Mirza, Rafia (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2024)
.